Healthcare expenses for treatment of acute myeloid leukemia. Issue 8 (3rd August 2019) - Bewersdorf, Jan Philipp; Shallis, Rory M.; Wang, Rong; Huntington, Scott F.; Perreault, Sarah; Ma, Xiaomei; Zeidan, Amer M.
ABSTRACT: Introduction : The cost of acute myeloid leukemia (AML) treatment is substantial and increasing. Inpatient treatment costs for allogeneic hematopoietic stem cell transplant (HSCT) and intensive chemotherapy are the main cost drivers in AML, however this pattern may change as new, expensive oral therapies enter the market. Areas covered : The authors provide an overview of the healthcare costs in patients with AML treated with various modalities (intensive chemotherapy, allogeneic HSCT, low-intensity treatment and supportive care only). The authors review both the impact of the recently approved novel AML agents and an increasingly personalized treatment approach on healthcare resources. Finally, the authors discuss whether these treatments are cost-effective from a societal perspective and how the increase in AML-associated costs can potentially be slowed. Expert opinion : The direct healthcare costs of AML are substantial and vary depending on the treatment approach, the country studied, and in the United States, a patient's insurance status. Treatment costs have increased out of proportion to general inflation and this trend is likely going to continue or even accelerate. Societal consensus on cost-effectiveness is essential. It remains to be seen how advances in diagnostic techniques and the incorporation of novel agents will impact medical outcomes, costs and influence health policy.